2020
DOI: 10.1029/2020gl087357
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Construction Has Reduced Organic Carbon Deposition in the East China Sea by Half Since 2006

Abstract: River‐dominated marginal seas are important carbon sinks on Earth. However, their carbon sequestration capacities are changing due to increased anthropogenic perturbations. Herein, we employ substantial datasets to study the characteristics of organic carbon (OC) from the East China Sea (ECS) in 2006 and 2018 and reveal the impacts of reservoir construction on the OC deposition in this region. We show that the distribution of sedimentary OC in the ECS is primarily controlled by riverine input and seabed erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It is worth noting that rapid decrease of sediment load from the Changjiang and Yellow Rivers has been considered as an important factor influencing present and future OC burial (Li et al., 2015; Sun et al., 2020; Wang et al., 2020). In particular, after impoundments of the Three Gorges Reservoir (TGR) in 2003 and Xiaolangdi Reservoir in 1999, sediment loads in the Changjiang and Yellow Rivers sharply decreased and kept at very low values relative to pre‐dam building period (Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that rapid decrease of sediment load from the Changjiang and Yellow Rivers has been considered as an important factor influencing present and future OC burial (Li et al., 2015; Sun et al., 2020; Wang et al., 2020). In particular, after impoundments of the Three Gorges Reservoir (TGR) in 2003 and Xiaolangdi Reservoir in 1999, sediment loads in the Changjiang and Yellow Rivers sharply decreased and kept at very low values relative to pre‐dam building period (Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…As human activities intensify, the preservation of OC in river-influenced inner shelf mud areas will be severely affected. Prior studies have found that watershed engineering (e.g., dam construction) can significantly change the sedimentary dynamic environment (Wang et al, 2020). In 2018, the OC deposition flux in the ECS shelf area decreased by ∼45% compared with that before the operation ( 2006) of the Three Gorges Dam (Wang et al, 2020).…”
Section: Implications For the Burial Of Oc In Marginal Seasmentioning
confidence: 99%
“…Prior studies have found that watershed engineering (e.g., dam construction) can significantly change the sedimentary dynamic environment (Wang et al, 2020). In 2018, the OC deposition flux in the ECS shelf area decreased by ∼45% compared with that before the operation ( 2006) of the Three Gorges Dam (Wang et al, 2020). The reduction in terrestrial particle inputs exacerbates seabed erosion and sediment mobilization.…”
Section: Implications For the Burial Of Oc In Marginal Seasmentioning
confidence: 99%
See 2 more Smart Citations